1988
DOI: 10.1071/bi9880571
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Antibody to Bluetongue Virus in New South Wales. II. Coastal Region and Age Distribution Surveys

Abstract: Three surveys of cattle for bluetongue (BLU) antibody were conducted over the years [1978][1979][1980] in coastal areas of New South Wales. In each survey the samples were identified by age.The prevalence of BLU-group antibody, demonstrated in a gel diffusion precipitin test, was highest in the north and decreased progressively to the south. Antibody prevalence increased with age. However, according to variations in prevalence by age and region, it was concluded that the activity of relevant viruses was highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…Convincing serological evidence that BLU-l infections occurred in 1980 was also found. These findings confirm previous conclusions, based on single-bleed surveys Littlejohns and Burton 1988), that both BLU-l and BLU-21 had infected cattle in this State. The presence of viruses of the EHD group had not previously been suspected but, from the results of this work, they may be more commonly responsible for inducing antibody reactive in the BLU GDP test than are those of the BLU group itself.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Convincing serological evidence that BLU-l infections occurred in 1980 was also found. These findings confirm previous conclusions, based on single-bleed surveys Littlejohns and Burton 1988), that both BLU-l and BLU-21 had infected cattle in this State. The presence of viruses of the EHD group had not previously been suspected but, from the results of this work, they may be more commonly responsible for inducing antibody reactive in the BLU GDP test than are those of the BLU group itself.…”
Section: Discussionsupporting
confidence: 83%
“…Its geographic distribution and annual variations in its prevalence and distribution have been described by Burton and Littlejohns (1988) and Littlejohns and Burton (1988). GDP tests for BLU have generally been considered to be group-specific (Klontz et al 1963;Jochim 1976) and the antigen used in the work reported here was shown by Sharp et al (1988) to be shared by two other Australian BLU virus serotypes, but not by three members of the Palyam (PAL) group.…”
Section: Introductionmentioning
confidence: 97%